2015
DOI: 10.1039/c5ra07683h
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent functionalization of carbon nano-onions with pyrene–BODIPY dyads for biological imaging

Abstract: We report a novel approach based on non-covalent interactions for the functionalization of carbon nano-onions (CNOs) with fluorophores. The assembly of pyrene-BODIPY conjugates on the CNO surface by means of pi-pi-stacking results in fluorescent carbon nanoparticles that are successfully uptaken by HeLa cancer cells with no cytotoxicity observed. The ability to functionalize carbon-based nanomaterials by using mild conditions will pave the way for future clinical application of these versatile nanomaterials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…These composites showed long‐term stability and very high dispersion in polar solvents . In addition, it was reported that non‐covalent modification of the CNO surface using pyrene‐BODIPY, 1,4‐naphthoquinone or 9,10‐phenanthrenoquinone changes their hydrophobic properties . Composites containing CNOs and polyelectrolytes, such as poly(diallyldimethylammonium chloride) (PDDA) or chitosan (Chit), were also obtained ,.…”
Section: Covalent and Non‐covalent Functionalization Of Cnosmentioning
confidence: 99%
See 4 more Smart Citations
“…These composites showed long‐term stability and very high dispersion in polar solvents . In addition, it was reported that non‐covalent modification of the CNO surface using pyrene‐BODIPY, 1,4‐naphthoquinone or 9,10‐phenanthrenoquinone changes their hydrophobic properties . Composites containing CNOs and polyelectrolytes, such as poly(diallyldimethylammonium chloride) (PDDA) or chitosan (Chit), were also obtained ,.…”
Section: Covalent and Non‐covalent Functionalization Of Cnosmentioning
confidence: 99%
“…The nuclei were stained with Hoechst 33342, while lysosomes were stained with Lysotracker red probe. Scale bar represents 10 μm . Reprinted from Refs.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations